Consumer Satisfaction Using e-Wallets - Heru Kresnha Reza; Melly Susanti (PT FORMOSA CENDEKIA GLOBAL, 2022)
According to Ministerial Regulation No. 14 of 2017 IKM is a tool to measure the level of community satisfaction as service users and improve the quality of public services. The purpose of this study was to measure the level of community satisfaction in the village. Calculation Method Satisfaction value is